Progression of malrotation into volvulus in an adult after appendectomy - Basa, Johanna (Oxford University Press, 2014)
Among the pediatric population malrotation is the most common cause of volvulus. This paper describes a case of adult malrotation, which progressed to volvulus shortly after appendectomy. It also reviews clinical presentations and diagnostic tools, discusses the recommended management, and considerations when addressing of this rare malady.